Automatic buffet tray cover / Amir Shukri Mohd Nasir - Mohd Nasir, Mohd Nasir (2023)
Buffet trays are widely used in restaurants today, but there are several drawbacks that must be considered. Using the buffet cover correctly, flies fall in dishes and contaminate food and having bad habits of not putting things back are just a few of the drawbacks. By implementing an automatic mechanism, the buffet tray Buffet trays are widely used in restaurants today, but there are several drawbacks that must be considered. Using the buffet cover correctly, having flies fall in dishes and contaminate food, and having bad habits of not putting things back are just a few of the drawbacks. By implementing an automatic mechanism, the buffet lid will automatically close when the ladle of side dishes is placed in its position, so resolving the issue. Both the restaurant owner and the customer can gain from this since the restaurant owner can ensure that the food is prepared in hygienic condition and the customer can avoid contracting food poisoning, especially if it affects youngsters or the elderly. This project will use the method of designing in SOLIDWORKS software and by using this software simulation, it could tell if the design is successful or not successful